The idea of a regular army and the pamphlet war in England during the late 17th – early 18th centuries - D.O. Gordienko (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to the attitude of the British public to the problem of creation and development of a regular army in the Three Kingdoms during the second half of 17th – early 18th centuries. After the civil wars in the middle of the 17th century, the regular army institution was established in England. The problem of army and tyranny favored by it was little discussed in the English press until 1688 because of the censorship. After the Glorious Revolution, criticism or apologetics of the idea of creating a regular royal army became an interesting and popular theme for British pamphlets. In the late 17th century, John Trenchard was the leading author, who criticized the regular army as a tool of tyranny. Daniel Defoe, who defended the view that armed forces are needed to defend the state and religious independence of Great Britain, developed an active debate with him. Many other publicists both actively supported and opposed regular army establishment in the Three Kingdoms. The problem remained relevant to the British public until the second half of the 18th century.